Inequality, welfare and income distribution experimental approaches - Cowell, Frank A. (Research on economic inequality ;, 2004)
The emerging literature on experimental methods in connection with economic inequality has shed fresh light on how to think about inequality, how important issues of equality are in comparison with other economic objectives and how individuals incorporate criteria of equality and fairness into their own decisions. This volume covers a wide range of topics in the field of income distribution and extends the approach to related issues such as mobility and attitudes to risk. The selection of papers includes both participatory experiments - where individuals respond to economic incentives - and questionnaire experiments designed to investigate the extent to which individuals' values and attitudes conform to the way that economists and others conventionally model inequality and welfare.